Dead meat - Coe, Sue 1951- (Four Walls Eight Windows, 1995)
Armed with her sketchbook, Sue Coe traveled across the United States, following the path from factory farm to feedlot, to the "killing floor" of the slaughterhouse. Her firsthand observations are rendered in her diaries and artwork - stunning, unforgettable images. Dead Meat graphically documents the castrations, debeakings, electrocutions, and decapitations; the skewing, flaying, and dismembering; the pathos and tragedy. Coe made eye contact with a frightened veal calf awaiting execution and talked to the people who commit the sanctioned killing that supplies our meat-eating culture. Her illustrations evoke the dark, cavernous abattoir, slippery with blood, steam, and body heat. Workers wielding knives and stun guns slave in dangerous conditions, dehumanized by the brutality of their jobs, alienated by economic oppression. Like Upton Sinclair's The Jungle, Dead Meat indicts the system of corruption and consumption that exacts such a toll from its citizens.
Keywords: Coe, Sue <1951-> -- Political and social views; Coe, Sue -- 1951-; Meat industry and trade in art; Schlachthof; Malerei; USA; Bildband